Analisis Kesalahan Gramatikal dalam Penulisan Ilmiah Mahasiswa - Khamid, Nur (Jurnal Ilmiah Citra Ilmu, 2021)
As it is known, there are still many students who do not understand how to write descriptions in English. Within that framework, this research was conducted to determine the extent of grammatical errors in morphological and syntactic aspects, the most prominent errors and to find out the causes of errors. The writing technique used purpose sampling where the researcher took 33 samples from 600 populations. From the research results, morphological and syntactic errors were found. The errors were caused, among others: difficulty understanding grammar, composing sentences, mastering vocabulary, memorizing formulas, teachers not clearly explaining, students lack of learning, class atmosphere is not conducive and lack of practice or practice. So that students make many mistakes in writing English descriptions. This condition must be understood and addressed as it is. In the future, a deeper study is needed to evaluate the English learning program so that students can better master writing English descriptions.